TMIC-54. THE ROLE OF TUMOR MICROENVIRONMENT DERIVED GROWTH FACTORS IN PEDIATRIC BRAIN TUMORS. (14th November 2022) - Cruz, Andrea; Locke, Abigail; Halligan, Katharine; Sanders, Lauren; Cheney, Allison; Stanton, Ann-Catherine Jean; Koncar, Robert; Broniscer, Alberto; Vaske, Olena M; Pearce, Thomas; Marker, Daniel; Wiley, Clayton; et al.
Abstract: BACKGROUND: High-grade gliomas (HGGs) are the most common fatal intrinsic brain tumors in pediatric patients. H3K27-altered diffuse midline gliomas (H3K27-DMGs), a subgroup of HGGs defined by a histone 3 position 27 alteration, are especially aggressive and result in the poorest patient outcomes. Despite in-depth genomic characterization, the 5-year survival rate has yet to improve beyond 2% following diagnosis. A common feature of H3K27-DMGs is infiltration of microglia, macrophages, other myeloid cells, collectively referred to as GAMs, and a small population of T-cells. The contribution of non-tumor cells in the tumor microenvironment (TME) can both promote and or inhibit tumor growth, thus representing an opportunity in the pursuit of novel therapeutics. Using bioinformatic analysis on a human H3K37-DMG single cell-RNA sequencing dataset, we reveal several cell-to-cell communication signaling networks, mediated by ligand and receptor pairs, between GAMs and tumor cells, respectively. HYPOTHESIS: Microglial-derived growth factors activate oncogenic signaling pathways via paracrine signaling axes, thus promoting H3K27-DMG tumor cell proliferation and growth. METHODS: I will validate these findings and test their therapeutic potential using co-culture studies, CRISPR and shRNA gene silencing, and phospho-proteomics technology. RELEVANCE: This research provides further insights on the contribution of non-tumor cells in the TME towards H3K27-DMG cell proliferation and growth and could potentially inform future therapy paradigms.